Poems to Siva : The Hymns of the Tamil Saints - Peterson, Indira Viswanathan, 1950- (Book collections on Project MUSE., 2014)
Composed by three poet-saints between the sixth and eighth centuries A.D., the Tevaram hymns are the primary scripture of the Tamil Saivism, one of the first popular large-scale devotional movements within Hinduism. Indira Peterson eloquently renders into English a substantial portion of these hymns, which provide vivid and moving portraits of the images, myths, rites, and adoration of Siva and which continue to be loved and sung by the millions of followers of the Tamil Saiva tradition. Her introduction and annotations illuminate the work's literary, religious, and cultural contexts, makin.